Proposta de solução para manutenção de defeitos funcionais na BR-404 na zona rural do município de Iguatu/CE - Bezerra, Cândida Maria Alves de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Although in Brazil, asphalt paving is the most used, preserving its quality has not yet been a priority, as it is common the appearance of defects such as cracks, potholes, sags, caused possibly because by the poor quality execution and maintenance services, or even the lack thereof. Such defects, according with Bernucci et al. (2010), can compromise the pavement life and cause irreparable damage to users. This paper presents a solution proposal for the asphalt pavement maintenance in a stretch of highway BR-404, located in the city of Iguatu/CE, very used for people and cargo traffic. Its purpose is to evaluate the pavement regarding its functionality by Global Severity Index (IGG), Surface State Index (IES) and International Roughness Index (IRI), and relate them for that the proposed maintenance alternative can be determined. The methods used to perform the work consist of evaluations performed according with DNIT specifications and theoretical references. Subjective assessment surface of flexible and semi-rigid pavements, the continuous visual survey and the longitudinal irregularity evaluation were performed. And then appropriate maintenance solution was determined. From the evaluations carried, out it was determined that the stretch pavement has a state ranging from bad to very bad, and has no longitudinal irregularity. Therefore, in general, it was observed that the pavement of the evalueted stretch has significant defects, which promote unfavorable conditions of functionality, and that, due to the high degree of degradation, the reconstruction of the coating is necessary.
Monografia
Keywords: Revestimento asfáltico; Defeitos; Avaliação; Funcionalidade; ENGENHARIAS::ENGENHARIA CIVIL